Pengaruh NPM, ROA, ROE, dan Ukuran Perusahaan Terhadap Harga Saham Perusahaan Yang Tergolong Dalam Indeks LQ45 - Dila Adelia; Moh. Iskak Elly; Feni Wilamsari (Komunitas Dosen Indonesia, 2025)
This study aims to examine the effect of NPM, ROA, ROE and Company Scale on the share price of companies classified in the LQ45 index during the 2019-2023 period. The method used in this research is panel data regression analysis using quantitative methods. The total research subjects include 45 companies. The sample was selected using purposive sampling and 18 companies were observed for 5 years, so the total information tested was 90 information. The information testing method used in this study includes statistical review, mean difference test, and conjecture difference test where information processing is assisted by using EViews software version 13. The results of this study indicate that ROA has a significant positive effect on stock prices (t = 2.717456 sig = 0.0083) while NPM, ROE, and company size have no effect on stock prices. simultaneously the four variables explain 54.02% of stock prices (Adjusted R square = 0.540264).